The effect of brassinosteroid on cucumber (Cucumis sativus) growth under varying water availability - AULIA NURROHMAH; SOLICHATUN SOLICHATUN; ARI PITOYO (Smujo International, 2026)
Abstract. Nurrohmah A, Solichatun, Pitoyo A. 2026. The effect of brassinosteroid on cucumber (Cucumis sativus) growth under varying water availability. Asian J Agric 10 (1): g100144. https://doi.org/10.13057/asianjagric/g100144. Cucumber (Cucumis sativus) is a horticultural crop belonging the family Cucurbitaceae and is widely consumed in Indonesia. Cucumber production in the country tends to fluctuate due to extreme climate conditions, which cause variations in water availability and consequently disrupt plant growth. One approach to enhance cucumber tolerance to fluctuating water conditions is the application of brassinosteroid. This study aimed to evaluate the effects and determine the most effective concentration of brassinosteroid on cucumber growth under different level of water availability. A Completely Randomized Design (CRD) was employed with two factors and four replications. The first factor was field capacity (100%, 60%, and 40%), and the second was brassinosteroid (0, 0.5, 1, and 2 ppm). Cucumbers were grown for 40 days after transplanting and brassinosteroid was applied weekly as a foliar spray to the leaf surface. Data were analyzed using two-way Analysis of Variance (ANOVA) and followed by one-way unstucked ANOVA at a significance level of P < 0.05. Then tested by Duncan’s Multiple Range Test (DMRT) at a 95% confidence level. The Correlation analysis used Spearman's rank correlation coefficient. The results showed that brassinosteroid significantly improved cucumber growth parameters under different water availabilities. A brassinosteroid concentration of 0.5 ppm was most effective in improving vegetative growth parameters and plant biomass at 60% field capacity, while also increasing chlorophyll content under well-watered conditions (100% field capacity). In contrast, a higher concentration of 2 ppm promoted proline accumulation at 40% field capacity. The research suggest that lower brassinosteroid promote cucumber growth under moderate, whereas higher concentrations facilitate osmotic adjustment under severe drought conditions.